Star Wars Episode 3 : Revenge of the Sith - Patricia C. Wrede (London, United Kingdom Cornerstone, 2005)
Possibly the most anticipated Star Wars movie of all time, Star Wars: Episode III Revenge of the Sith at last tells the tale of how the young Jedi Anakin Skywalker became Darth Vader, the most feared villain in the galaxy. Our novel includes material not in the movie, based on discussions with George Lucas himself. Based on the screenplay of the movie, Star Wars: Episode III Revenge of the Sith, the novel brings the epic full circle, revealing at last just how the young Jedi, Anakin Skywalker, became the most evil villain in the galaxy, Darth Vader, and father to Luke and Leia. When the novel opens, the Clone Wars are still in full cry, and numerous Jedi have already been lost. Anakin is struggling with his dual life: Jedi Knight and husband (in secret) to Padme Amidala. The time is drawing near for the machiavellian Darth Sidious--the Sith Lord determined to wrest control of the galaxy from the Republic--to draw tight the noose he has been creating around Anakin Skywalker...and create a new Sith Lord with unmatched dark-side Force powers...
Keywords: Science Fiction, Fantasy; Science Fiction -- Science Fiction; Fantasy -- Fantasy